Land's end : capitalist relations on an indigenous frontier - Li, Tania, 1959- (Duke University Press, 2014)
An intimate account of the emergence of capitalist relations among indigenous highlanders in Indonesia who privatized their common land to plant a boom crop, cacao. Spurred by the hope of ending their poverty and isolation, some prospered, while others lost their land and struggled to sustain their families. Tania Murray Li's richly peopled ethnography takes the reader into the highlanders' world, exploring the dilemmas they faced as sharp inequalities emerged among them.